2020
DOI: 10.1093/jat/bkaa088
|View full text |Cite
|
Sign up to set email alerts
|

Toxic Metal-Containing Particles in Aerosols from Pod-Type Electronic Cigarettes

Abstract: The popularity of electronic cigarettes (electronic nicotine delivery systems or ENDS) has grown rapidly over the past decade. With the continued evolution of ENDS, and the arrival of newer replaceable pod devices on the market, it is prudent to examine their emissions to help determine potential health risks to the user. Metal containing particles were examined in aerosol from several pod-based devices from three manufacturers that offer flavored liquids in their respective products. Previous ENDS metal emiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 17 publications
3
31
0
Order By: Relevance
“…RPE cells in vivo are known to contain melanin pigment while ARPE-19 cells lack any visible pigmentation. It would be necessary to evaluate the effects of e-liquids on pigmented RPE, especially as melanin is known to have affinity for metals [ 83 ] and it has been reported that several trace metals, such as nickel, chromium, lead, and copper are present in e-liquids [ 84 , 85 , 86 , 87 ]. Hence, the cytotoxicity profile of the flavors with and without nicotine will need to be determined in the physiological environment utilizing primary RPE cells for the future.…”
Section: Discussionmentioning
confidence: 99%
“…RPE cells in vivo are known to contain melanin pigment while ARPE-19 cells lack any visible pigmentation. It would be necessary to evaluate the effects of e-liquids on pigmented RPE, especially as melanin is known to have affinity for metals [ 83 ] and it has been reported that several trace metals, such as nickel, chromium, lead, and copper are present in e-liquids [ 84 , 85 , 86 , 87 ]. Hence, the cytotoxicity profile of the flavors with and without nicotine will need to be determined in the physiological environment utilizing primary RPE cells for the future.…”
Section: Discussionmentioning
confidence: 99%
“…Studies using methods with well determined limits of detection also indicated that the corrosive nature of the liquid toward metal device components in contact with the liquids as well as the ages of the devices were important factors that contributed to liquid and aerosol metal concentrations [ 7 , 8 ]. Studies of aerosols using single particle and dual element single particle inductively coupled plasma-mass spectrometry (SP-ICP-MS) provided evidence that electrical connectors and other device components, other than the heating element, were the more likely sources of chromium or nickel containing particles [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Other data support that the nichrome from the heating elements is resistant to oxidation (even at high temperatures) and suggest other alloys as possible sources of chromium, iron, and nickel oxide. However, the authors cannot exclude a limited degree of degradation of nichrome heating elements caused by extensive use periods [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…E-cigarette aerosols contain nanoparticles (11–25 nm median diameter) and submicron particles (96–175 nm median diameter) [ 20 ]. The size of the inhaled particles is important for the depth of airway penetration, and the toxic potential can be enhanced by the high penetration of small-sized particles in tissues and organs [ 21 , 22 ]. Re et al found a connection between chronic e-cigarette aerosol exposure and endogen metal dyshomeostasis, which has been linked to the onset of neurodegenerative diseases, such as Alzheimer’s and Parkinson’s [ 19 ].…”
Section: Introductionmentioning
confidence: 99%